#TITLE_ALTERNATIVE# - YUSUF (NIM 10301007), MUHAMMAD
The Hartmann Test was invented by J. Hartmann in 1904 and applied to the 80cm Postdam refractor. It represented the first truly scientific method of analysing image quality in operational telescopes in that it supplied direct quantitative results. In modified forms, it remains today the basis of the most accurate measures of telescope image quality. This process employs a mask to turn star test images into spot patterns. These inside and outside of focus spot patterns could now be compared and used to mathematically determine how much of which aberration exists at each spot on the system. These spots can be graphically connected using a method calling ray-tracing. Hartmann has introduced a criterion T, for quantitative quality, defined as the weighted mean diameter, expressed in hundred-thousandths of the focal length, of the cones of light from various zone in plane where the circle of light containing all of the converging pencils is smallest. High quality optics was classically defined as having T 0.5 (Fox 1908) or 0.2 (Wilson 1999).